Coinage metal complexes of NHC-stabilized silyliumylidene ions. Issue 97 (25th October 2018) - Frisch, Philipp; Inoue, Shigeyoshi
Abstract : The first coinage metal complexes (M = Cu, Ag, Au) of an N-heterocyclic carbene-stabilized silyliumylidene ion are reported. Abstract : The first silyliumylidene ion coinage metal complexes are reported. Treatment of N-heterocyclic carbene (NHC) stabilized silyliumylidene ions (R = m -Ter, Tipp) with transition metal precursors (CuCl, AgOTf, (Me2 S)AuCl) yields the first silyliumylidene coinage metal (M = Cu, Ag, Au) complexes, which have been fully characterized including X-ray diffraction analyses.